Implementasi Pengelolaan PPH 21, PPH 22, dan PPH 23 di Dinas Pemberdayaan Masyarakat dan Desa Provinsi Riau - Nadia Fitri Ramadani; R Septian Armel (CV. Rayyan Dwi Bharata, 2024)
PPH ensures that every individual or legal entity that owns wealth contributes to the financing of the state, so that the tax burden is evenly distributed across society and supports economic stability and general welfare. This is achieved by ensuring that any taxable transactions are fairly and clearly assigned to domestic taxpayers or permanent establishments. In addition, it promotes financial stability. Riau Province's Community and Village Empowerment Office conducted this investigation. The study looked at the system and management of PPh 21, 22, and 23 tax burdens. It was conducted from June to July 2024. The Dinas's Financial Data Application (ADK) and Daily and Monthly Transaction Recapitulation (RTHA DTH) used observations, interviews, and instructions to collect data for this study. Preliminary data was also derived from a qualitative descriptive approach. Articles 22 and 23 of Income Tax provide BPKD with the tax payable from relevant transactions, such as the purchase of goods and services, in accordance with the provisions of the applicable tax regulations. This is done to support clear and reliable regional financial management and ensure compliance with tax obligations. Riau Province's Community and Village Empowerment Agency brings together PPH 21, 22, and 23. The reports are sent via DJP Online e-Filing. The purpose of this process is to ensure tax regulations apply to the income of the individual or company being taxed.